Advanced wordprocessing desktop publishing 2101 : teaching guide - Newfoundland and Labrador. Department of Education. (Government of Newfoundland and Labrador, Department of Education, Division of Program Development, 1992)
Advanced Wordprocessing Desktop Publishing 2101 Teaching Guide